Histopathological study of the effect of sunitinib in treatment of retinal angiogenesis induced by VEGF 165 in rabbits’eyes - Shahad Salah Aldeen; Mustafa Ghazi Alabbassi (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2018)
Eye is one of the important sensory structures in the body which responsible for vision through its anterior and posterior chambers. Retinal angiogenesis is the development of new, abnormal blood vessels in the retina that considered the pathological feature of different ocular diseases such as diabetic retinopathy, the major cause of vision loss in the world. The diseases were diagnosed by different methods and the treatment includes anti-angiogenic drugs and surgical therapy. This study was designed by dividing twenty-four rabbits in to four groups each with six rabbits; control (PBS-administered) group, angiogenic (VEGF-administered) group, ranibizumab-treated group, sunitinib-treated group. The result showed that there is absence of angiogenesis in sunitinib-treated group, which were similar to ranibizumab-treated group when compared with angiogenic group. The result explains the anti-angiogenic activity of sunitinib due to its blocking effect on VEGFRs.one can conclude from this study that sunitinib can be used in treatment of retinal angiogenic diseases in future.